Reasons for and time to retraction of genetics articles published between 1970 and 2018 - Dal-Ré, Rafael (J Med Genet, 2019)
INTRODUCTION: Between 0.02% and 0.04% of articles are retracted. We aim to: (a) describe the reasons for retraction of genetics articles and the time elapsed between the publication of an article and that of the retraction notice because of research misconduct (ie, fabrication, falsification, plagiarism); and (b) compare all these variables between retracted medical genetics (MG) and non-medical genetics (NMG) articles. METHODS: All retracted genetics articles published between 1970 and 2018 were retrieved from the Retraction Watch database. The reasons for retraction were fabrication/falsification, plagiarism, duplication, unreliability, and authorship issues. Articles subject to investigation by company/institution, journal, US Office for Research Integrity or third party were also retrieved. RESULTS: 1582 retracted genetics articles (MG, n=690; NMG, n=892) were identified . Research misconduct and duplication were involved in 33% and 24% of retracted papers, respectively; 37% were subject to investigation. Only 0.8% of articles involved both fabrication/falsification and plagiarism. In this century the incidence of both plagiarism and duplication increased statistically significantly in genetics retracted articles; conversely, fabrication/falsification was significantly reduced. Time to retraction due to scientific misconduct was statistically significantly shorter in the period 2006–2018 compared with 1970–2000. Fabrication/falsification was statistically significantly more common in NMG (28%) than in MG (19%) articles. MG articles were significantly more frequently investigated (45%) than NMG articles (31%). Time to retraction of articles due to fabrication/falsification was significantly shorter for MG (mean 4.7 years) than for NMG (mean 6.4 years) articles; no differences for plagiarism (mean 2.3 years) were found. The USA (mainly NMG articles) and China (mainly MG articles) accounted for the largest number of retracted articles. CONCLUSION: Genetics is a discipline with a high article retraction rate (estimated retraction rate 0.15%). Fabrication/falsification and plagiarism were almost mutually exclusive reasons for article retraction. Retracted MG articles were more frequently subject to investigation than NMG articles. Retracted articles due to fabrication/falsification required 2.0–2.8 times longer to retract than when plagiarism was involved.